Development of COPS board game on learning organic chemistry synthetic pathways among matriculation students - Rajakumar Ramachandran (2022)
This study aims to develop Synthetic Pathways of Organic Compounds (COPS) and investigate matriculation students perceptions towards the board game. The research employed the developmental design based on ADDIE model. A total of 171 respondents participated in this study where data were gathered via four types of questionnaire. The needs analysis survey on 36 chemistry educators revealed 86.1% of them required or had intention to use GBL in their organic chemistry lessons and 91.7% agreed on suitability of GBL for the same purpose. After designing and developing COPS, a questionnaire was administered among five experts whom averagely scored 90.8% of agreement on its validity. Pilot study on 30 respondents showed high reliability coefficient ( = 0.993). One hundred and five matriculation students strongly agreed that COPS has positive impact on learning organic synthetic pathways with high mean scores for all the five constructs. Findings showed mean scores and standard deviations for goals, board design, board organisation, playability, and usability were M=4.46; SD=0.707, M=4.42; SD=0.745, M=4.31; SD=0.811, M=4.46; SD=0.747, and M=4.37; SD=0.770 respectively. In conclusion, COPS was perceived as a useful learning tool for organic synthetic pathways. The study implies COPS would be able to offer more fun and joyful learning environment in teaching and learning of the topic.